Reaktualisasi Konsep Recht Idee Gustav Radbruch Sebagai Fondasi Hukum Progresif Indonesia - Adiansyah Adiansyah; Abdul Kadir Jailani; Hendra Darmawan; Erdy Nopriady; Delima Santri; A. Jabidi Ritonga (SENTRI: Jurnal Riset Ilmiah, 2026)
The problem of law enforcement in Indonesia, which is still stuck in a formalistic approach, shows the need for a strong philosophical foundation to support progressive law. This study examines how Gustav Radbruch's concept of recht idee can be reactivated as the foundation of progressive law in Indonesia. Using normative legal research methods with a philosophical and conceptual approach, this study analyzes the relationship between Radbruch's thinking on the three basic values of law, namely justice, utility, and legal certainty, with Satjipto Rahardjo's ideas on progressive law. Radbruch developed the principle of priority, which allows justice to take precedence when it conflicts with legal certainty, even stating that natural law can override positive law if it contradicts fundamental justice. This thinking is in line with progressive law, which rejects the deification of legal texts and prioritizes substantive justice. The results of the study show that the reactivation of Radbruch's concept of recht idee provides philosophical legitimacy for progressive legal breakthroughs and strengthens the theoretical basis for breaking free from the shackles of formalism. Thus, the Indonesian legal system can realize laws that are truly fair and beneficial to society.